Pengaruh Fraksi Volume Serat Buah Lontar terhadap Kekuatan Tarik dan Kekuatan Impak Komposit Bermatrik Polyester - Bella, Yustian; Suprapto, Wahyono; Wahyudi, Slamet (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
In the industrial world nowadays, natural fiber has been widely developed as an important part in the preparation of composite material. Lontar Fruit is a natural commodity enriched with fiber but still less maximally utilized. Lontar Fruit fiber is then composed with polyester matrix to be an alternative material to the preparation of polymer-based helmet and gas tube. Research attempts to examine the tensile and impact strengths of this application. In this research, therefore, polyester resin is composed with Lontar Fruit fiber and this composite is treated with alkali 5 % NaOH for 30 minutes. Preliminary test has indicated that the tensile strength of genuine single fiber (without treatment) is 33.3 N/mm2 and the maximal tensile strength of single fiber is 36.96 N/mm2 after treatment with alkali 5 % NaOH for 30 minutes. After this preliminary test, the composite is then tested by treating Lontar Fruit fiber with alkali 5 % NaOH for 30 minutes upset time against various volume fractions of Lontar Fruit fiber, respectively at 0 %, 5 %, 15 %, 25 % and 35%. It is then by the results, the favorable mechanic attributes, precisely the tensile strength and impact strength of the polyester matriculated composite with Lontar Fruit fiber as the reinforce, can be explained as follows. The best tensile strength of the composite is 47.7 MPa found at volume fraction variation of 15 %. The best impact strength of the composite is 30.1519179 J observed at volume fraction of 35 %.Keywords: Lontar Fruit Fiber,Tensile Strenght, Impact Strenght, Composite